PORTARIA PRPB Nº 326, DE 15 DE DEZEMBRO DE 2016. - Rodolfo Alves Silva (DOU, 19/12/2016, Seção 2, p. 49, 2016)
Designar servidora requisitada para a Função de Assistente - Nível II, FC-2, da PRM-Sousa.